Methods and techniquesAtrioventricular nodal reentrant tachycardia ablation with radiofrequency energy during ongoing tachycardia: is it feasible? - Amasyali, Basri; Kilic, Ayhan; Kabul, Kutsi; Unlu, Murat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : Radiofrequency (RF) ablation of the slow pathway for treatment of atrioventricular nodal reentrant tachycardia (AVNRT) is conventionally performed during sinus rhythm. Aim : To evaluate the clinical and electrophysiological features and the short- and long-term results of slow pathway RF ablation during ongoing AVNRT. Material and methods : A total of 282 consecutive patients with AVNRT undergoing RF catheter ablation were analysed. Patients whose tachycardia episodes could not be controlled during RF energy application and who underwent slow pathway ablation or modification during ongoing tachycardia formed the study group (group 1, n = 16) and those ablated during sinus rhythm formed the control group (group 2, n = 266). Results : Of the clinical characteristics, only the frequency of tachycardia attacks was higher in group 1 (3.3 ±1.2 vs. 2.1 ±0.9 attacks/month, p < 0.001). Among the baseline electrophysiological measurements, the echo zone lasted significantly longer in group 1 than in group 2 (78 ±25 ms vs. 47 ±18 ms; p 0.050 for all). All patients were followed-up for 29 ±7 months; only 2 patients ( 0.050). No permanent atrioventricular block was observed. Conclusions : The RF catheter ablation or modification of the slow pathway during ongoing AVNRT is feasible with acceptable short- and long-term efficacy and safety. However, this approach needs to be clarified with large-scale studies.